Reliability and validity of physiological data obtained within a cycle-run transition test in age-group triathletes - Vleck, V.; Millet, G. P.; Bessone Alves, F.; Bentley, D. J. (Journal of Sports Science & Medicine, 2012)
This study examined the validity and reliability of a sequential "Run-Bike-Run" test (RBR) in age-group triathletes. Eight Olympic distance (OD) specialists (age 30.0 ± 2.0 years, mass 75.6 ± 1.6 kg, run VO2max 63.8 ± 1.9 ml/kg·min, cycle VO2peak 56.7 ± 5.1 ml/kg·min) performed four trials over 10 days. Trial 1 (TRVO2max) was an incremental treadmill running test. Trials 2 and 3 (RBR1 and RBR2) involved: 1) a 7-min run at 15 km/h (R1) plus a 1-min transition to 2) cycling to fatigue (2 W/kg body mass then 30 W each 3 min); 3) 10-min cycling at 3 W/kg (Bsubmax); another 1-min transition and 4) a second 7-min run at 15 km/h (R2). Trial 4 (TT) was a 30-min cycle - 20-min run time trial. No significant differences in absolute oxygen uptake (VO2), heart rate (HR), or blood lactate concentration ([BLA]) were evidenced between RBR1 and RBR2. For all measured physiological variables, the limits of agreement were similar, and the mean differences were physiologically unimportant, between trials. Low levels of test-retest error (i.e. ICC <0.8, CV<10%) were observed for most (logged) measurements. However [BLA] post R1 (ICC 0.87, CV 25.1%), [BLA] post Bsubmax (ICC 0.99, CV 16.31) and [BLA] post R2 (ICC 0.51, CV 22.9%) were least reliable. These error ranges may help coaches detect real changes in training status over time. Moreover, RBR test variables can be used to predict discipline specific and overall TT performance. Cycle VO2peak, cycle peak power output, and the change between R1 and R2 (deltaR1R2) in [BLA] were most highly related to overall TT distance (r = 0.89, p < 0. 01; r = 0.94, p < 0.02; r = 0.86, p < 0.05, respectively). The percentage of TR VO2max at 15 km/h, and deltaR1R2 HR, were also related to run TT distance (r = -0.83 and 0.86, both p < 0.05).